The Determinants of the Long Term Private Investment in Brazil: An Empyrical Analysis Using Cross-section and a Monte Carlo Simulation - Braga Tadeu, Hugo Ferreira (2013)
Empirical studies regarding the determinants of private investment in developing countries, including Brazil, have demonstrated the high inflation’s rates negative impact on investment. However, the recent Brazilian’s experience clearly shows that stabilization is not capable of recovering investment’s rates. Therefore, the objectives of this study are: a) to analyze the long term private investment’s determinants in Bra zil; b) analyze if the Brazilian economy has been impacted by the crowding-in or crowding-out effetcs; and c) analyze the macronomic variables’ behavior during the 2012 to 2017 period. In order to do this, we used a cross section econometric analysis and a Monte Carlo Simulation for the data analysis. The paper presents the main investment theories, and recent developments of these theories, as well as how they can be applied to the Brazilian data. The results show evidences of a public investment crowding-in effect in infrastructure over the private investment. All the analyzed variables’ signs are consistent with the theory, with the exception of the real interest’s rates, where the coefficient is positive and insignificant in the estimated equation. The reduction in the credit’s volume and the existence of political and economic instabilities showed that they are harmful to private investment in the analyzed period. The implementation of public policies in order to guarantee economic stability and improve the government’s credibility, along with the increase of credit offer, could boost private investment in Brazil. DOI: https://doi.org/10.1016/S2077-1886(13)70025-8